Issues and challenges in management of waqf organisations in Ningxia Province of China - Ma, Binghai (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Waqf institutions in China are facing several issues and challenges such as waste of charitable resources, difficulties in retaining Waqf assets, and low levels of professionalism of those involved in Waqf. The major reason for such problems is poor management mechanisms or mechanisms that are antagonistic to development of Waqf in China. The internal management mechanisms of these institutions continue to be designed and controlled to support personal ambitions and control as opposed to the more religious considerations advocated by Islam that align with the purpose of Waqf. Despite this formidable challenge that permeates Waqf in China, there has been a lack of research on these issues. This study aims to fill this lacuna in the literature by investigating and assessing the management mechanism and national governance of both general and Islamic aspects of Waqf in China. The study adopts a qualitative method using semi-structured interviews with five respondents comprising three managers of Waqf institutions and two religious consultants. The managers are from the Ningxia Hui Autonomous Region of China, while the religious consultants are among the most authoritative consultants who work with important institutions or organisations. The interview is conducted in Mandarin and is translated into English. The findings highlight several issues and challenges facing Waqf in China, including the lack of a defined aim, low level of capability and professionalism, narrow-mindedness, and poor levels of coordination. Other issues include brain drain, unstable performance, low qualification, and managerial neglect of Waqf managers. Lastly, the findings elaborate the relationships between China's national governance and Islamic governance. The findings of this study provide important inputs for the regulators and managers as well as Muslim scholars to improve the management of Waqf and enhancing its role in in efforts to establish a better image of Muslims in the Chinese society.